Predictors of Remission in Rheumatoid Arthritis Patients Treated with Biologics: : A Systematic Review and Meta-Analysis - Khader, Yasmin (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.